HOW TO CREATE CONDITIONS FOR DEVELOPMENT OF MINING SECTOR THROUGH ADMINISTRATIVE REFORMS - Serikbayeva, Assel (Nazarbayev University Graduate School of Public Policy, 2017)
The topic of achieving sustainable development and growth in natural resource abundant countries has received considerable attention from scholars and policy makers alike. Most commodity exporters have followed a variety of policies and recommendations in numerous attempts to achieve economic growth and spillovers to the rest of the economy. This Master thesis argues that industrial development should start from development of a competitive mining sector. Kazakhstan has abundant mineral and hydrocarbon base. While its oil industry is relatively developed, the mineral sector has not achieved its potential despite the large reserves. Large parts of the current mineral legislation and tax regime are uncommon in an international practice and deter investment. This Master thesis carries out a comparative analysis of the Kazakhstan’s mining regime in terms of legislation, fiscal framework, and non-tax benefits. The paper makes recommendations on changes that should be made to achieve a world class mining industry and mimic the development path of resource rich industrialized countries.
Keywords: natural resource; economic growth; industrial development; competitive mining sector; oil industry